2017
DOI: 10.1108/itp-02-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Group size and personalization’s effect on Facebook message response rates

Abstract: Purpose The bystander effect is one of the most well researched and replicated phenomena in social psychology. It repeatedly shows that the presence of other people inhibits the impulse to help due to the concept of diffusion of responsibility. Recently, researchers have studied this phenomenon online in the context of e-mails, internet chat rooms, and discussion forums. The results provide evidence that the presence of “virtual” others decreases the likelihood of helping behavior. Personalization is another f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Joinson and Reips's findings are validated by various other studies: personalization supports response rates (Heerwegh et al 2005;Dillman et al 2007;Joinson and Reips 2007;Fatkin 2017;Barron and Yechiam 2002;Muñoz-Leiva et al 2009).…”
Section: Incentives and Personalizationsupporting
confidence: 58%
“…Joinson and Reips's findings are validated by various other studies: personalization supports response rates (Heerwegh et al 2005;Dillman et al 2007;Joinson and Reips 2007;Fatkin 2017;Barron and Yechiam 2002;Muñoz-Leiva et al 2009).…”
Section: Incentives and Personalizationsupporting
confidence: 58%
“…Third, this study contributes to the research on WOM by demonstrating that individuals' response behaviors toward help-requests embedded in HMCs can take the form of proactive helping, reactive helping, or inaction. Most of the existing WOM studies focus on increasing individuals' response rates (Fatkin and Lansdown, 2017) and consider individuals' responses to marketing campaigns as a binary concept, such as purchase (Yang, 2022) and sharing (Wang et al ., 2021). Based on the dichotomy of reactive and proactive behaviors (Spitzmuller and Van Dyne, 2013), this study depicts recipients' responses to HMCs as proactive helping, reactive helping and inaction.…”
Section: Discussionmentioning
confidence: 99%
“…SNGs also enable individuated communication (e.g. identifying one recipient using a tag or name) which is found to mitigate the responsibility diffusion effect (Fatkin and Lansdown, 2017). Thus, request individuation (i.e.…”
mentioning
confidence: 99%
“…Bild et al (2015) studied aggregate user behavior and the retweet graph focusing on quantitative descriptions to understand retweeting. The study of Fatkin and Lansdown (2017) suggested that personalizing is an effective way to elicit more responses in online environments.…”
Section: Information Diffusion In Osnmentioning
confidence: 99%